Stent Graft Modification to Preserve Intercostal Arteries Using Thoracoabdominal Off-the-Shelf Multibranched (t-Branch) Endograft. (June 2021) - Ferreira, Marcelo; Mannarino, Matheus; Cunha, Rodrigo; Ferreira, Diego; Capotorto, Luis Fernando; Oderich, Gustavo S.
Purpose: To demonstrate an off-the-shelf multibranched (t-Branch) modification to allow intercostal arteries preservation during juxtarenal, pararenal, paravisceral, and extent IV thoracoabdominal aortic aneurysm repair.Technique: The t-Branch is an off-the-shelf device not customized for specific patient anatomy and may be offered for urgent endovascular repair for patients with complex aortic aneurysms. However, a concern when treating patients who do not aneurysms extending above the celiac axis is that the more proximal extension which is required with this device may render patients at high risk for spinal cord injury. We report a novel technique with t-Branch modification performing a 180° fabric back windows at the first 2 sealing stents that allow perfusion to the intercostal arteries.Conclusion: T-Branch-PIA (preserving intercostal arteries) modification limits intercostal arteries coverage while optimizing proximal seal zone in juxtarenal, pararenal, paravisceral, and extent IV thoracoabdominal aneurysms, thereby may decrease the risk of spinal cord injury.